Development of refractory ceramics from residual silica derived from rice husk ash and steel fibres. Issue 16 (November 2017) - Stochero, N.P.; Marangon, E.; Nunes, A.S.; Tier, M.D.
Abstract: Despite their high hardness and thermal stability, refractory ceramics have a tendency to undergo failure due to fatigue and thermal shock. In this study, the effects of rice husk silica and steel fibres on the mechanical and thermal properties of refractory ceramic materials were investigated. Samples were fabricated by replacing kaolin clay with 20% rice husk silica and 3%, 6% or 9% steel fibres in volume percentages. These specimens were analysed for their mineralogical composition, density, apparent porosity, tensile strength in a three-point bending test, thermal shock and microstructural analysis by scanning electron microscopy. For materials with silica and clay, a reduction in porosity and increase in mechanical resistance was observed. Ceramics with 9% steel fibre had the greatest ductility, while materials with 3% and 6% steel fibre presented the highest resistance against thermal shock.